International Organizations and Educational Change in Spain during the 1960s - Gómez-Escalonilla, Lorenzo (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2020)
From the end of the 1950s, Spain’s political leaders felt the need to promote changes in the educational system that would bring it up to date and give more space to practical content and technical training. International organizations played a leading role in the propagation of these new ideas and organizational practices for the training of human capital and its contribution to economic development. The reports and guidelines of the OECD and UNESCO disseminated prior experiences on educational planning carried out in Latin America, at the same time that they functioned as channels for the transmission of knowledge and teaching methods throughout the 1960s. The modernizing sectors of the Francoist elite (the technocrats) were the main liaisons with those international organizations. They were convinced that it was necessary to reform an obsolete and class-based system to adapt it to the demands of a society that was undergoing a strong process of economic growth. Such schemes, likewise, proved useful to the political project of authoritarian modernization that was propping up the Franco dictatorship. This text will examine the relationship of the Spanish state with the international organizations that provided advice and funding to undertake a set of changes in education, changes that would culminate in the General Education Law of 1970 at the start of the following decade.